Advertisements and Their Effectiveness Among Young People: An Example of a Message About Aid Activities Related to The War in Ukraine - Marzena WANAGOS (Communications of International Proceedings, 2022)
In the conditions of increasing access to the media, advertising continues to play an important role in the transmission of information. Public service announcement is a special form that aims to induce socially desirable changes, promote positive patterns of behavior, attitudes or draw attention to various social problems. Such information is used by both non-profit organizations, local governments, the government and participants of the commercial market. In the face of the war in Ukraine, Polish media quite often appeared in messages showing the activities of various institutions to help refugees or the possibilities of support in Ukraine by Polish citizens. A specific group of recipients are young people who have specific behaviors and usually do not want to take up difficult topics. The main aim of the article was to examine the impact of selected social advertisements on the declared changes in recipient behavior. In this study, an attempt was made to examine their reaction to the media message in the form of social advertisements, which contained information about the war in Ukraine. 274 students from four general secondary schools in Gdańsk, Sopot and Gdynia were examined. The students ranged in age from 17-19. The study was carried out using the diagnostic council method in the form of a direct questionnaire. The study shows that the surveyed group showed great empathy for refugees, most of the respondents received such an advertisement positively. Almost all agreed that such information is needed. A large group of respondents showed active help.
Keywords: public service announcement; refugees; effectiveness of social advertising; young people